Dentinal microcracks formation in the root canal in chemical mechanical preparation with protaper universal, protaper next and twisted file adaptive - Jara Castro, Marisa (2016)
Object: evaluate the formation of microcracks in the dental root canal after chemical mechanical pre-paration with Protaper Universal, Protaper Next and TF Adaptive systems. Then to determine which systems generates fewer microcracks after chemical mechanical preparation. Materials and méthod: 38 freshly extracted mandibular premolars, which have a single root canal were selected. The sample was divided into three for each chemical mechanical preparation system experimental groups (n = 11). Group A: Protaper Universal Group B: Protaper Next, Group C: Adaptive TF. And a fourth group (n = 5) corresponding to the negative control group. After chemical mechanical preparation horizontal slices 4mm, 8mm and 12mm from the apex, which were evaluated with a 20x stereomicroscope where the presence of microcracks was determined were performed. Results: The Protaper Universival produces microcracks compared to Protaper Next and Adaptive TF with a statistically significant difference (P >.05). At 12mm the Adaptive TF system has more micro cracks without being this statistically sig-nificant. Conclusions: The Next Protaper and Twisted File Adaptive systems tend to generate fewer microcracks dentin compared to Protaper Universal system in the apical third.